Simulasi Perhitungan Waktu Salat Menggunakan Spreadsheet - Raisal, Abu Yazid; Ariswan, Ariswan; Sukma, Mega; Ritonga, Marataon (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2022)
The determination of prayer times initially only used the direct observation method (rukyat) namely observing the shadow of an object, then the determination of prayer times developed with the advent of the calculation method (hisab). The purpose of this study is to make a simulation of the calculation of prayer times using a spreadsheet. A simulation of the calculation of prayer times using a spreadsheet has been made. The prayer times generated by the spreadsheet are not much different from the prayer times obtained from the Accurate Times application. The simulation that has been made can show the effect of the Earth's revolution at prayer times at various latitudes.